Defect, Diffusion and Dopant Properties of NaNiO2: Atomistic Simulation Study - Kaushalya, R.; Iyngaran, P.; Kuganathan, N.; Chroneos, A. (Energies, 2019)
Abstract: Sodium nickelate, NaNiO2, is a candidate cathode material for sodium ion batteries due to its high volumetric and gravimetric energy density. The use of atomistic simulation techniques allows the examination of the defect energetics, Na-ion diffusion and dopant properties within the crystal. Here, we show that the lowest energy intrinsic defect process is the Na-Ni anti-site. The Na Frenkel, which introduces Na vacancies in the lattice, is found to be the second most favourable defect process and this process is higher in energy only by 0.16 eV than the anti-site defect. Favourable Na-ion diffusion barrier of 0.67 eV in the ab plane indicates that the Na-ion diffusion in this material is relatively fast. Favourable divalent dopant on the Ni site is Co2+ that increases additional Na, leading to high capacity. The formation of Na vacancies can be facilitated by doping Ti4+ on the Ni site. The promising isovalent dopant on the Ni site is Ga3+.
Keywords: NaNiO2; Defects; Na diffusion; Dopants; Atomistic simulation